Causal relationship model of Chinese generation Z undergraduates’ academic motivations - Wu, Tingting; Niramitchainont, Poschanan (Kasetsart Journal of Social Sciences, 2026)
It is critical to acknowledge that academic motivation is a foundational element influencing learners’ learning engagement, outcomes as well as educators’ effective instruction. However, Generation Z (Gen Z) undergraduates are reported lacking of academic motivation in some areas of China. As motivation is an intrinsic psychological process closely related to personal emotions, psychological perceptions and needs, this paper attempts to analyze academic emotions and learning motivation via basic psychological needs in order to enhance Gen Z academic motivation. This paper adopts a quantitative research method among a sample of 960 Gen Z undergraduates in Guangxi Province, China, through the Achievement emotions questionnaire, Basic psychological needs satisfaction scale and Academic motivation scale (college version) to investigate the correlations among variables including academic emotions, need for competence, autonomy, and relatedness as well as academic motivation. The results demonstrate that the causal relationship model partially matches the data set well, as illustrated by the fit indices. Furthermore, the findings showed that academic emotions could predict academic motivation through competence and relatedness needs except for autonomy. Additionally, while academic emotions could predict academic motivation through competence and relatedness; nevertheless, academic emotions fail to predict academic motivation through competence and autonomy. Therefore, educators in higher education need to realize the cultural variances in the roles of basic psychological needs of Gen Z undergraduates in China, particularly autonomy satisfaction.